The Effectiveness of The Implementation of Child-Friendly Schools in Preventing Bullying Behavior at SDN Salammulya Purwakarta - Epi Saepul Mustopa; Pian Firman Hidayat; Suharyanto Soro; Dinny Mardiana (Civiliza Publishing, Indonesia., 2025)
Bullying behavior in the elementary school environment is a serious problem that has an impact on the psychological and social development of students. Child-Friendly Schools are here as a strategic approach to create a safe, inclusive, and violence-free educational environment. This study aims to analyze the effectiveness of the implementation of child-friendly schools in preventing bullying behavior. The research uses a qualitative approach with a case study method. Data were collected through observations, in-depth interviews, and documentation studies. Determination of responders using purposive sampling technique. The principal respondents were chosen because they were managers, teachers were selected based on class rank, and students were selected based on the position of class leader in the upper class. The results of the study show that the organization of the program is carried out systematically and participatory, involving the principal, teachers, students, and parents. Structured program coordination with the appointment of coordinators and monthly regular meetings. Implementation has been proven to be effective in preventing bullying through character building, positive habituation, and gradual case handling that integrates anti-bullying education and intensive communication with parents is . Key supporting factors include the principal's policies, a clear coordination structure, and planned case management. However, the main obstacle is the limitation of child-friendly facilities and infrastructure, which schools overcome through adaptive strategies. Conclusion: The implementation of Child-Friendly Schools at Salammulya State Elementary School is quite effective in preventing bullying behavior, although it is still constrained by limited facilities and infrastructure